The Influence of Cisplatin Dose upon Survival in Concurrent Chemoradiotherapy of Locally Advanced Cervical Carcinoma with Weekly Cisplatin - Igor Sirák (Acta Medica, 2008)
The objective of this study was to evaluate the influence of cisplatin dose upon 3-year overall and disease-free survival rate of patients with advanced cervical cancer treated with concurrent chemoradiotherapy with weekly cisplatin. Seventy-three patients with stage IIB – IVA cervical carcinoma were treated with pelvic (or pelvic + paraaortic) externalbeam radiotherapy, high-dose rate brachytherapy and concomitant chemotherapy with weekly cisplatin of 40 mg/m2 in the time period form January 2000 to December 2006 at our department. The 3-year overall survival and disease-free suvival rates were evaluated with regard to the number of cisplatin cycles applied during the external radiotherapy. Only twentyeight patients received the intended five doses of chemotherapy. The most frequent cause of chemotherapy delay was the acute hematological toxicity with leukopenia. The 3-year overall survival was 71 % and the 3-year disease-free survival was 61 %. Survival analyses didn’t prove a statistically significant influence of cisplatin dose upon 3-year survival in cervical carcinoma patients treated by exclusive chemoradiation with weekly cisplatin.